Bacterial Antagonist Isolates in Controlling Bacterial Wilt Disease of Potato (Ralstonia solanacearum) in Aeroponic Cultivation System - Nurbaya Nurbaya; Tutik Kuswinanti; Baharuddin Baharuddin (Hasanuddin University, 2013)
The growing of potato plants in aeroponics system is considered as safe and ecologically friendly for producing natural, healthy plants and crops. However, it often faces with several constraints. Infection of bacterial wilt caused by Ralstonia solanacearum in the aeroponics cultivation system can spread rapidly through the nutrition flow and lead to plant death and crop failure. The objective of this study was to evaluate bacterial antagonist isolates belonging to Clostridium sp in reducing bacterial wilt disease of potato caused by Ralstonia solanacearum in aeroponic system and its effect on increasing the weight and number of potato tubers. The results showed that of the seven treatments tested on potato aeroponic system, treatment with a combination of isolates NS01 + G06 + S06 tend to be more effective in suppression of bacterial wilt disease (85%), increase the amount of seed tubers (162.5 tubers/treatment) and increase the average of tuber weight as much as 311.25 gr/treatment. It can therefore be concluded that a combination of three isolates of Clostridium sp i.e: NS01 + G06 + S06 had some synergic activities in potato aeroponic cultivation system.